1998
DOI: 10.1017/s0317167100034004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Six Novel SOD1 Gene Mutations in Familial Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by the premature death of motor neurons. In approximately 10% of the cases the disease is inherited as autosomal dominant trait (FALS). It has been found that mutations in the Cu/Zn superoxide dismutase gene (SODl) are responsible for approximately 15% of FALS kindreds. We screened affected individuals from 70 unrelated FALS kindreds and identified 10 mutations, 6 of which are novel. Surprisingly, we have found a mutation in exon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…A similar type of mutation has been documented by Boukaftane et al, 1 who found a deletion in intron 4 of three nucleotides 30-bp downstream of the exon-intron splice junction in a FALS patient, but they did not investigate the mRNA levels.…”
supporting
confidence: 61%
“…A similar type of mutation has been documented by Boukaftane et al, 1 who found a deletion in intron 4 of three nucleotides 30-bp downstream of the exon-intron splice junction in a FALS patient, but they did not investigate the mRNA levels.…”
supporting
confidence: 61%
“…Segregation of the mutations could not be confirmed in the families presented here, because of the death of the affected members. The conservation of Asp at codon 101 and Gly at codon 141 among various species [25] suggests that these amino acids are essential for the proper function of SOD1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, at present 119 (108 + 11) SOD1 mutations have been associated with ALS (ALSOD) and are presumed to be causative, but many are private mutations found in single families and validation is lacking [9,[19][20][21][22][23][24]. The 119 mutations are scattered all over the molecule with predilection for exons 4 and 5.…”
Section: Copper-zinc Superoxide Dismutase (Sod1)mentioning
confidence: 99%
“…In heavily inbred families, three patients homozygous for the L84F, N86S, and L126S mutations have been reported, whereas other patients have been heterozygous [20,34,35]. Tragically, when these mutations appear in homozygous form, the resulting disease has sudden onset and extremely fast progression to death.…”
Section: Copper-zinc Superoxide Dismutase (Sod1)mentioning
confidence: 99%